Introduction to mass spectrometry 1 - Ruotolo, Brandon T. (Henry Stewart Talks, 2026)
Mass Spectrometry (MS), Mass spectrum, Mass-to-charge (m/z) ratio of ions, Ion sources in mass spectroscopy, Mass resolving power and mass resolution, Electron Impact Ionization (EI), Chemical Ionization (CI), Electrospray Ionization (ESI), Matrix-assisted Laser Desorption Ionization (MALDI)